Characterisation of Cutibacterium acnes phylotypes in acne and in vivo exploratory evaluation of Myrtacine®. (12th June 2018) - Pécastaings, S.; Roques, C.; Nocera, Th.; Peraud, C.; Mengeaud, V.; Khammari, A.; Dréno, B.
Abstract: Objective: Our main objective was to compare Cutibacterium acnes ( C. acnes ) skin colonisation in patients with mild to moderate acne versus healthy controls and secondly, to evaluate a Myrtacine ® ‐based cream on C. acnes total population and antibioresistant Cutibacteria in patients with acne. Methods: In 60 acne patients (Global Acne Severity Scale, GEA grades 2–3), of mean age 20 [15–30] years and in 24 age‐ and sex‐ matched healthy controls, forehead strips samplings were performed for microbiological analysis of comedones by colony forming unit (CFU) counts of global C. acnes and erythromycin (EryR) or clindamycin‐resistant (ClnR) populations of Cutibacterium and determination of phylotypes by MALTI‐TOF. Clinical evaluations of acne patients (GEA, lesion count, porphyrin fluorescence) were performed at baseline and after 56 days of twice‐daily application of a Myrtacine ® ‐based cream. Results: We first showed (i) high and similar levels of C. acnes colonisation in superficial pilosebaceous follicles and detection of EryR and ClnR strains in both acne and control groups; (ii) different repartition of phylotypes in acne patients versus healthy control, with a predominance of phylotype IA in acne patients and a link between phylotype IA and erythromycin resistance. Besides, after treatment with the Myrtacine ® ‐based cream in acne patients, there was no change in C. acnes total load, but a significant decrease of EryR Cutibacteria, reduced porphyrin production by C. acnes, a decrease in acne severity (GEA), associated with reduced retentional and inflammatory lesions. Conclusion: Cutibacterium acnes colonisation was not significantly different in acne versus control groups. Phylotype IA was predominant in acne patient and in EryR C. acnes . A Myrtacine ® ‐based cream significantly reduced the level of EryR Cutibacteria in vivo and improved acne lesions.